O Moderno do Antigo: A estesia cívica do jovem Almeida Garrett nas Revoluções Liberais ibéricas - Joana Duarte Bernardes (Carnets)
If Romanticism seemed to announce the advent of the “new”, the “ancient” never ceased to be called for. That is the case of anti-Napoleonic movements, a voice of the “new” featuring the “ancient” through its meanings and forms. In order to prove it, we will privilege literary texts, focusing on Almeida Garrett, taking into account their canonic principles and their conceptual vocabulary (homeland, patriotism, revolution, tyranny, despotism, freedom, etc.). However, if this is a terminology eminently under the influence of the Classics, it also inspired the vocabulary of the Modern, mainly for the Liberals, in Spain (Cadiz Constitution, 1812) and in Portugal (1820-22), who superimpose its usage to the employ coined by the anti-Napoleonic traditionalists.